1993
DOI: 10.1111/j.1432-1033.1993.tb17765.x
|View full text |Cite
|
Sign up to set email alerts
|

1H‐NMR spectroscopy of bovine lens β‐crystallin

Abstract: 'H-NMR spectroscopic studies of bovine eye lens P-crystallin aggregates (dimer, trimer and octomer) are presented. The NMR spectra for all three P-crystallin aggregates are dominated by resonances from the pB2 subunit, particularly from the N-and C-terminal extensions of this subunit. Resonances from other subunits, which all have terminal extensions, are, in general, absent from spectra of the P-crystallin aggregates. Therefore, the @2 subunit and, in particular its terminal extensions, has enhanced flexibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 21 publications
3
20
0
Order By: Relevance
“…However, the function of the Nterminal extensions of β-crystallins remains unknown. They may play a role in stabilization of β-crystallin oligomers, but this hypothesis is still under investigation (Cooper, Carver and Truscott, 1993 ;Kroone et al, 1994 ;Trinkl, Glockshuber and Jaenicke, 1994 ;Werten et al, 1996 ;Ajaz et al, 1997). The Nterminal extensions may also act as intermolecular spacers to keep crystallins in elongating lens fibers dispersed.…”
Section: Discussionmentioning
confidence: 95%
“…However, the function of the Nterminal extensions of β-crystallins remains unknown. They may play a role in stabilization of β-crystallin oligomers, but this hypothesis is still under investigation (Cooper, Carver and Truscott, 1993 ;Kroone et al, 1994 ;Trinkl, Glockshuber and Jaenicke, 1994 ;Werten et al, 1996 ;Ajaz et al, 1997). The Nterminal extensions may also act as intermolecular spacers to keep crystallins in elongating lens fibers dispersed.…”
Section: Discussionmentioning
confidence: 95%
“…The asparagine-proline sequence in ␤B2 occurs at the interface between the N-terminal extension and the first "Greek key" containing motif (22). 1 H NMR spectroscopy has confirmed that the Nterminal extensions of ␤-crystallins have relatively greater flexibility than the Greek key containing motifs (31). Therefore, the proteolytically resistant Asn 15 -Pro 16 region of ␤B2 may be relatively inaccessible compared to the Asn-Pro regions of ␤B1 and ␤A3 which are cleaved.…”
Section: Discussionmentioning
confidence: 99%
“…The long N-terminal extension of bB1 is rapidly cleaved and by 1 year of age, 50 % of bB1 within a human lens has lost 15 amino acids from the N-terminus (David et al, 1996;Lampi et al, 1998). Several studies have shown that b-crystallin extensions facilitate higher ordered associations (Cooper, Carver and Truscott, 1993;Ajaz et al, 1997;Werten et al, 1999) and that loss of the N-terminal extension of bB1 is correlated to a decrease in the bH aggregate (Ajaz et al, 1997;Lampi et al, 1998;Ma et al, 1998). Thus, modi®cations to bB1 are associated with changes in oligomer formation.…”
Section: Introductionmentioning
confidence: 90%